INTERNATIONAL ORGANIZATIONS AS A CENTER OF NETWORK DIPLOMACY - Kunina Irina Aleksandrovna (Modern Scientific Technology, 2024)
The low efficiency and non-compliance with the requirements of the reality of today's classical formats of international cooperation have revealed the need for new designs of multilateral and multi-level formats. One of such structures of multilateral cooperation, in which participants in international relations on an equal basis, using flexible tools, are aimed at solving urgent problems, is network diplomacy. Even though it is the States that play a key role in the system of international relations, the system is much more complex in its structure, given the multilevel and multidimensional relationships. In addition to States, international organizations, actors of non-governmental diplomacy, institutions of club diplomacy and groups of states (for example, the Group of Twenty and BRICS) today make up this complex system, and therefore the global governance system is becoming more diversified, and network structures are more diverse.